Control of cell shape, neurite outgrowth, and migration by a Nogo-A/HSPG iInteraction - Kempf, Anissa; Boda, Enrica; Tews, Björn (Developmental cell, 2017)
Summary Heparan sulfate proteoglycans (HSPGs) critically modulate adhesion-, growth-, and migration-related processes. Here, we show that the transmembrane protein, Nogo-A, inhibits neurite outgrowth and cell spreading in neurons and Nogo-A-responsive cell lines via HSPGs. The extracellular, active 180 amino acid Nogo-A region, named Nogo-A-Δ20, binds to heparin and brain-derived heparan sulfate glycosaminoglycans (GAGs) but not to the closely related chondroitin sulfate GAGs. HSPGs are required for Nogo-A-Δ20-induced inhibition of adhesion, cell spreading, and neurite outgrowth, as well as for RhoA activation. Surprisingly, we show that Nogo-A-Δ20 can act via HSPGs independently of its receptor, Sphingosine-1-Phosphate receptor 2 (S1PR2). We thereby identify the HSPG family members syndecan-3 and syndecan-4 as functional receptors for Nogo-A-Δ20. Finally, we show in explant cultures ex vivo that Nogo-A-Δ20 promotes the migration of neuroblasts via HSPGs but not S1PR2.
Gesehen am 07.08.2018